Analisis Kemampuan Siswa dalam Menyelesaikan Soal Tentang Ilmu Ekonomi di SMA Negeri 16 Palembang - Belleantari, Nanda; Hodsay, Zahruddin; Permatasari, Nuryanti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Student ability is an individual's capacity to complete learning tasks that encompass cognitive, affective, and psychomotor aspects. This study aims to analyse students' ability to solve Economics questions on the subject of needs at State Senior High School 16 Palembang. This study used a qualitative descriptive method. The research subjects consisted of 64 students in grades X.8 and X.9. Data collection techniques were carried out through written tests and documentation of student learning outcomes. The data were analysed by grouping the test results into ability categories based on the score range. The results showed that most students were able to complete the Economics questions well. A total of 22 students (34.37%) were in the excellent category with scores of 86–100, 16 students (25%) were in the good category with scores of 71–85, and 15 students (23.44%) were in the fair category with scores of 56–70. Meanwhile, 6 students (9.38%) were in the poor category and 5 students (7.81%) in the very poor category. The overall average score of the students was 78.43, which falls into the good category. Based on these results, it can be concluded that students at SMA Negeri 16 Palembang generally have good abilities in completing Economics questions on the subject matter.